The influence of sodium dichloroacetate on the oxidative processes in sarcoma 37 - Sorokina, L.V.; Pyatchanina, T.V.; Didenko, G.V.; Kaplia, A.A.; Khyzhnyak, S.V. (Experimental Oncology, 2011)
Aim: to study the activity of antioxidant enzymes and to evaluate an intensity of prooxidant processes in sarcoma 37 (S37) cells during tumor development and under influence of sodium dichloroacetate (SDA). Methods: Activity of total superoxide dismutase (SOD), SOD isoforms, catalase (Cat), glutathione peroxidase (GP), and glutathione reductase (GR), as well as content of reduced glutathione (GSH) and lipid peroxidation (LP) secondary byproducts were determined in S37 homogenated tissues of untreated mice and animals treated with SDA at daily dose of 86 mg/kg. Results: SDA treatment of S37-bearing mice resulted in the reduced activities of total SOD, SOD isoforms (especially Mn-SOD), Cat, GP and significantly decreased GSH content on the background of LP intensification in tumor tissue. Conclusion: The observed changes of oxidative homeostasis in S37-bearing animals treated with SDA could be considered as an element of antitumor action of SDA.